2020
DOI: 10.3390/ijms21238926
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Homeostasis in Plants

Abstract: Sulfur (S) is an essential macronutrient for plant growth and development. S is majorly absorbed as sulfate from soil, and is then translocated to plastids in leaves, where it is assimilated into organic products. Cysteine (Cys) is the first organic product generated from S, and it is used as a precursor to synthesize many S-containing metabolites with important biological functions, such as glutathione (GSH) and methionine (Met). The reduction of sulfate takes place in a two-step reaction involving a variety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 119 publications
(191 reference statements)
1
71
1
Order By: Relevance
“…Cysteine and glutathione metabolism are reported to indicate parallels with Allium flavour precursor biosynthesis [ 31 ]. Moreover, cysteine is the first organic product generated from S [ 32 ]. Cysteine synthase is the last enzyme of sulfate assimilation pathway, and O-acetylserine (OAS), the precursor of cysteine, is derived from the carbon and nitrogen assimilation pathways [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine and glutathione metabolism are reported to indicate parallels with Allium flavour precursor biosynthesis [ 31 ]. Moreover, cysteine is the first organic product generated from S [ 32 ]. Cysteine synthase is the last enzyme of sulfate assimilation pathway, and O-acetylserine (OAS), the precursor of cysteine, is derived from the carbon and nitrogen assimilation pathways [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, sulfur uptake, its assimilation and the effects of its deprivation have been widely and extensively treated in plants and in microalgae. Several studies on microalgae have revealed that S transporters and some enzymes of the S assimilation pathway show a negative feedback mechanism driven by S demand [19]. That is, for instance, in Chlorella sorokiniana the cysteine synthesis is repressed when sulfate is available and it is activated by S starvation [14,20].…”
Section: Introductionmentioning
confidence: 99%
“…Plants undergo a series of altered morphological and physiological processes under sulfur deficiency conditions [5], which can affect productivity. Plants adapt to sulfur deficiency by activating the assimilation and catabolism of stored sulfur compounds, and repressing the synthesis of secondary sulfur metabolites, such as glucosinolates [6].…”
Section: Introductionmentioning
confidence: 99%